Fast bidirectionally-decodable arithmetic coding with chaotic redundancy and threshold control - Yi YAN; Guofang TU; Can ZHANG; Shaoshuai GAO; Deyuan CHEN (Tongxin xuebao)
Although the JPEG2000 compression standard has high coding efficiency,its error resistance and security can’t meet the requirements of practical application.Based on this,a fast bidirectionally-decodable arithmetic coding method with chaotic redundancy and threshold control was proposed.At the encoder,the chaotic map controlled the probabilities of multiple redundant symbols to enhance the security of arithmetic coding.At the decoder,threshold control and bidirectional decoding were combined to realize fast decoding based on maximum a posteriori estimation.Simulation results show that the proposed method improves the reconstructed image quality with better error resistance and security.